The COVID-19 pandemic and social policy narratives in Costa Rica: the story of a (fleeting) opportunity - Martínez Franzoni, Juliana (2023)
Did the coronavirus disease (COVID-19) pandemic embolden ideas favourable to inclusive social policy in Latin America? This article addresses that question by examining the emergency cash transfer programme that was implemented in Costa Rica in 2020. Drawing on legislative debates and interviews with senior officials and analysts, the study reveals the fleeting emergence of ideas in favour of expanding non-contributory social protection. The new programme was quickly reined in by a discourse that assimilated fiscal responsibility to cutting social spending rather than expanding revenues. Avoiding simplistic generalizations, the findings invite a contextualized analysis of the impact of the pandemic on specific policy-making processes, and a consideration of the role of ideas in social policy debates. If there is a risk to inclusive social policy, it is the dominant discourse of austerity.